Aren Palm-Based Product Development Strategy to Support Agrotourism in Kekait, West Nusa Tenggara, Indonesia: Strategi Pengembangan Produk Berbasis Pohon Aren untuk Mendukung Agrowisata di Kekait, Nusa Tenggara Barat, Indonesia - Amaro, Moegiratul; Fatimah, Ai Imas Faidoh (Yayasan Siti Widhatul Faeha, 2025)
Palm sap (Arenga pinnata) plays a crucial role in sustaining local livelihoods and preserving cultural identity in Kekait Village, West Lombok. However, the development of this commodity remains limited by low product quality, inadequate processing technology, and weak integration with the village’s agrotourism sector, resulting in suboptimal economic benefits for the local community. This study aims to formulate a comprehensive development strategy for palm sap–based products to increase value-added and strengthen sustainable agrotourism. A narrative review method was applied by synthesizing primary data from field observations, semi-structured interviews, and community empowerment activities with secondary literature. The data were analyzed descriptively using SWOT analysis to examine key internal and external factors influencing the sector. The results show that technological interventions, such as the use of cabinet dryers and the application of Good Food Handling Practices, significantly enhance product shelf life and compliance with market standards. In addition, institutional strengthening, digital marketing, and the integration of cultural-based educational tourism are effective in expanding market access and improving competitiveness. The scientific contribution of this study lies in offering a holistic upstream–downstream development model grounded in community empowerment, positioning palm sap products not only as economic commodities but also as drivers of cultural preservation, environmental sustainability, and improved community welfare within agrotourism-based rural development.